Combined Adipose Tissue-Derived Mesenchymal Stem Cell Therapy and Rehabilitation in Experimental Stroke - Mu, Jingwei; Bakreen, Abdulhameed; Juntunen, Miia; Korhonen, Paula; Oinonen, Ella; Cui, Lili; Myllyniemi, Mikko; Zhao, Shanshan; Miettinen, Susanna; Jolkkonen, Jukka (Frontiers in Neurology, 2019)
Background/Objective: Stroke is a leading global cause of adult disability. As the population ages as well as suffers co-morbidities, it is expected that the stroke burden will increase further. There are no established safe and effective restorative treatments to facilitate a good functional outcome in stroke patients. Cell-based therapies, which have a wide therapeutic window, might benefit a large percentage of patients, especially if combined with different restorative strategies. In this study, we tested whether the therapeutic effect of human adipose tissue-derived mesenchymal stem cells (ADMSCs) could be further enhanced by rehabilitation in an experimental model of stroke. Methods: Focal cerebral ischemia was induced in adult male Sprague Dawley rats by permanently occluding the distal middle cerebral artery (MCAO). After the intravenous infusion of vehicle (n = 46) or ADMSCs (2 × 106) either at 2 (n = 37) or 7 (n = 7) days after the operation, half of the animals were housed in an enriched environment mimicking rehabilitation. Subsequently, their behavioral recovery was assessed by a neurological score, and performance in the cylinder and sticky label tests during a 42-day behavioral follow-up. At the end of the follow-up, rats were perfused for histology to assess the extent of angiogenesis (RECA-1), gliosis (GFAP), and glial scar formation. Results: No adverse effects were observed during the follow-up. Combined ADMSC therapy and rehabilitation improved forelimb use in the cylinder test in comparison to MCAO controls on post-operative days 21 and 42 (P < 0.01). In the sticky label test, ADMSCs and rehabilitation alone or together, significantly decreased the removal time as compared to MCAO controls on post-operative days 21 and 42. An early initiation of combined therapy seemed to be more effective. Infarct size, measured by MRI on post-operative days 1 and 43, did not differ between the experimental groups. Stereological counting revealed an ischemia-induced increase both in the density of blood vessels and the numbers of glial cells in the perilesional cortex, but there were no differences among MCAO groups. Glial scar volume was also similar in MCAO groups. Conclusion: Early delivery of ADMSCs and combined rehabilitation enhanced behavioral recovery in an experimental stroke model. The mechanisms underlying these treatment effects remain unknown.